Synthesis and study on cyclooxygenases inhibitory activity of N - phenylbenzohydrazide derivatives - Watcharin Diloknawarit (Prince of Songkla University, 2012)
Thesis (M.Pharm., Pharmaceutical Sciences)--Prince of Songkla University, 2010